2018
DOI: 10.24843/eeb.2018.v07.i09.p02
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dukungan Organisasi Terhadap Komitmen Organisasional Dan Kinerja Pegawai

Abstract: This study aims to analyze: (1) influence of organizational support to employee performance, (2) influence of organizational support to organizational commitment and (3) influence organizational commitment to employee performance. A total of 77 employees of the Department of Population and Civil Registration of Denpasar is used as a sample with sampling technique that is saturated sampling. The data obtained were analyzed by descriptive analysis and SEM-PLS. The result of this study found that organizational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
6
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 4 publications
8
6
0
12
Order By: Relevance
“…According to Chiang et al(2011), perceived organizational support is positively related to organizational commitment. These results are consistent with the research of Adhika and Riana(2016), Vitria (2017), Fahrizal and Utama (2017), Metria and Riana (Metria & Riana, 2018), found that organizational support has a significant positive effect on organizational commitment. Based on the explanation above, the researcher develops a hypothesis tied to organizational support as follows.…”
Section: Relationship Between Perceived Organizational Support and Or...supporting
confidence: 92%
“…According to Chiang et al(2011), perceived organizational support is positively related to organizational commitment. These results are consistent with the research of Adhika and Riana(2016), Vitria (2017), Fahrizal and Utama (2017), Metria and Riana (Metria & Riana, 2018), found that organizational support has a significant positive effect on organizational commitment. Based on the explanation above, the researcher develops a hypothesis tied to organizational support as follows.…”
Section: Relationship Between Perceived Organizational Support and Or...supporting
confidence: 92%
“…Saat karyawan merasakan dukungan yang diberikan oleh perusahaan baik dari segi lingkungan yang nyaman antara karyawan maupun tata pelaksanaan kegiatan pekerjaan yang mereka laksanakan [2]. Kinerja karyawan adalah kontribusi yang diberikan setiap karyawan agar dapat tercapai setiap tujuan dari organisasi tersebut [3]. Kinerja karyawan adalah kontribusi yang diberikan setiap karyawan agar dapat tercapai setiap tujuan dari organisasi tersebut [4].…”
unclassified
“…Memberikan pekerjaan individu yang nilainya tidak selaras dengan nilai dalam organisasi yang ada, maka akan cenderung menghasilkan pegawai/karyawan yang kurang memiliki komitmen dan tidak terpuaskan oleh pekerjaan mereka dan oleh organisasi tersebut. Penelitian ini sejalan dengan penelitian yang dilakukan oleh (6,10,13,(28)(29)(30) yang menemukan hasil bahwa komitmen organisasi berpengaruh positif terhadap kinerja pegawai.…”
Section: Pengaruh Komitmen Organisasi Terhadap Kinerja Keuanganunclassified